A method for detecting pore size distribution in micro / nano cellulose concentration process

CN116106196BActive Publication Date: 2026-11-03SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310016008.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-06
Publication Date
2026-11-03
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

Existing technologies struggle to accurately measure the pore size distribution during the concentration of micro/nanocellulose, especially when moisture is present. This leads to errors in pore volume calculations, impacting its applications in coatings, pharmaceuticals, electronic components, and food.

Method used

Differential scanning calorimetry combined with the Gibbs-Thomson equation was used to calculate the pore size distribution by detecting the thermal transformation of frozen bound water. The low melting temperature of water in the fiber pores was utilized to directly detect the concentrated micro/nanocellulose.

Benefits of technology

It enables accurate measurement of the pore size distribution of concentrated micro/nanocellulose, avoiding the agglomeration problem caused by complete drying, and provides more realistic pore structure information, supporting its application in coatings, pharmaceuticals, electronic components and food.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116106196B_ABST
    Figure CN116106196B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of methods for detecting the pore size distribution in the concentration process of micro / nano cellulose.The method comprises the following steps: the cellulose slurry is subjected to refining treatment, and micro / nano cellulose suspension is obtained;The suspension is concentrated, and micro / nano cellulose semi-solid is obtained;The pore size distribution of the obtained micro / nano cellulose semi-solid is detected by isothermal step melting method of differential scanning calorimetry;The heating rate during detection is 1 ℃ / min, the temperature range is-35 ℃~15 ℃, and the detection time is 1h~3h.Through the method of the present application, the micro / nano cellulose suspension is concentrated to form pores, and the micro / nano cellulose semi-solid is detected by DSC, the pore size range of the pores formed by the micro / nano cellulose semi-solid and the frozen bound water content under different pore sizes in the pores of the micro / nano cellulose semi-solid can be obtained.This technology helps to better understand the influence of concentration on the pore structure of fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of micro / nanocellulose, and specifically relates to a method for detecting the pore size distribution during the concentration process of micro / nanocellulose. Background Technology

[0002] Micro / nanocellulose (M / CNFs) are renewable natural polymers isolated from plant fibers. Due to their high aspect ratio, high specific surface area, high mechanical strength, and biocompatibility, they show great application potential in coatings, pharmaceuticals, electronic components, and food. The isolated M / CNFs have a large number of exposed hydrogen bonds on their surface, which makes them highly chemically reactive but also gives them gel properties. Therefore, M / CNFs can usually only exist in suspensions with a concentration of <3.0 wt%, which leads to problems in their transportation and storage. This has prompted research into different drying and concentration methods. However, complete drying causes M / CNFs to aggregate and become keratinized, preventing them from being well redispersed in water, thus limiting the large-scale industrial application of micro / nanocellulose. Furthermore, the drying process consumes a large amount of energy, so many studies have chosen to partially dehydrate nanocellulose (e.g., centrifugation, filtration, extrusion, and solvent evaporation) instead of complete drying. The structural and property changes of M / CNFs after dehydration have a significant impact on subsequent applications, such as enzyme accessibility to M / CNFs, and the mechanical and optical properties of M / CNFs after film formation. Therefore, measuring the changes in pore structure and properties of M / CNFs during concentration is of great significance for the industrial production and application of M / CNFs.

[0003] Currently, the main methods for measuring the porosity of M / CNFs are mercury intrusion porosimetry and BET nitrogen adsorption. However, these methods are applicable to completely dried M / CNFs and cannot be used for CNFs that still contain moisture after concentration. In addition, solute exclusion method and NMR relaxation method, which use polyethylene glycol as the main probe molecule, are gradually being used to measure the M / CNFs after concentration. However, these methods also have the disadvantages of not being able to accurately reflect the changes in fiber pore size and having errors in the calculated pore volume. Summary of the Invention

[0004] To address the shortcomings and deficiencies of existing technologies, this invention provides a method for detecting the pore size distribution during the concentration of micro / nanocellulose.

[0005] This method is based on the thermodynamic properties of water and the Gibbs-Thomson equation. After concentration and dehydration, the M / CNFs suspension forms pores. Due to the lower pressure at the curved interfaces within the pores, the water in the pores, i.e., frozen-bound water, has a lower melting temperature, and its transition temperature is lower than that of free water. Based on the inverse relationship between the decrease in the melting temperature of frozen-bound water and pore size, differential scanning calorimetry is used to measure the thermal transition of frozen-bound water, thereby calculating the change in frozen-bound water content and detecting changes in pore size distribution during the concentration of micro / nanocellulose.

[0006] Gibbs-Thomson equations:

[0007]

[0008] T0 is the melting temperature of water (273.15K), γ ls It is the surface energy of the ice-water interface (12.1 mJ / m). 2 ), ρ and H f These are the density and specific heat of fusion of frozen bound water, respectively, assumed to be the same as those of unbound water (1000 kg / m³). 3 , 334J / g), D is the diameter of the pore, and ΔT is the melting temperature (K) at which the temperature drops.

[0009] The objective of this invention is achieved through the following technical solutions.

[0010] A method for detecting the pore size distribution during the concentration of micro / nano cellulose includes the following steps:

[0011] (1) The cellulose slurry was milled to obtain a micro / nano cellulose suspension;

[0012] (2) The suspension obtained in step (1) is concentrated to obtain micro / nano cellulose semi-solid;

[0013] (3) The pore size distribution of the micro / nano cellulose semi-solid obtained in step (2) was detected by isothermal step melting method of differential scanning calorimetry.

[0014] The detection method is as follows: micro / nano cellulose semi-solid is placed in a sealed crucible, and the temperature is raised in the sample pan of a differential scanning calorimeter by isothermal step melting method to obtain heat flow and temperature curves; the heating rate is 1℃ / min, the temperature range is -35℃~15℃, and the detection time is 1h~3h.

[0015] (4) Integrate each endothermic peak of the obtained heat flow curve separately, and calculate the frozen bound water content at each temperature corresponding to the pore size according to the thermodynamic formula, so as to obtain the pore size distribution of micro / nanocellulose at each temperature stage.

[0016] Preferably, the cellulose pulp in step (1) is cellulose from hardwood, softwood or other biomass sources, and the concentration of the pulp after grinding is 0.5wt%-3.0wt%.

[0017] Preferably, after the concentration process in step (2), the process further includes the following steps before differential scanning calorimetry (DSC) is used for detection:

[0018] (a) The obtained semi-solid was redispersed to obtain a redispersed micro / nano cellulose suspension;

[0019] (b) The suspension obtained in step (a) is concentrated to obtain a secondary concentrated micro / nano cellulose semi-solid.

[0020] Preferably, the redispersibility method in step (a) is mechanical redispersibility, the concentration of the redispersible micro / nanocellulose suspension is 0.5 to 3.0 wt%, and the dispersion method employs one or more combinations of a high-speed emulsifier, a nano homogenizer, an ultrafine grinding mill, and a nano-microfluidic homogenizer.

[0021] Preferably, when using a high-speed emulsifier to mechanically redisperse micro / nanocellulose semi-solids, the concentration of the redispersed micro / nanocellulose suspension is 0.7–1.5 wt%, the redispersing rate is 3000–7000 r / min, and the dispersion time is 2–10 min.

[0022] Preferably, the concentration process described in this invention is either filtration concentration or centrifugal concentration, employing one or a combination of two methods: vacuum filtration or centrifuge; preferably, the centrifuge speed is 1000–10000 r / min; and the concentration time is 30–180 min.

[0023] Preferably, the solid content of the micro / nano cellulose semi-solid in step (2) and the secondary concentrated micro / nano cellulose semi-solid in step (b) is 10.0 wt%-30.0 wt%.

[0024] Preferably, in step (4), each endothermic peak of the obtained heat flow curve is integrated individually using Origin software; the aperture corresponding to each temperature in step (4) is calculated according to the Gibbs-Thomson equation.

[0025] Preferably, the calculation process based on the thermodynamic formula in step (4) is as follows:

[0026] ① Calculate the total heat at each temperature stage based on the integral area and sample mass:

[0027] H t =ΔS×m

[0028] H t: Total heat at each temperature stage (J); ΔS: Integral area (J / g); m: Sample mass (g)

[0029] ② Calculate the specific heat capacity C of the sample. P :

[0030] Because the water in CNFs does not melt in the -30℃ to -20℃ range, the integral result corresponding to this range is used to determine the sensible heat of the sample and to calculate its specific heat capacity C. P :

[0031] Q -30~-20 =ΔS×m

[0032] Q -30~-20 : Heat absorbed by the sample during the -30℃ to -20℃ range (J); ΔS: Integral area (J / g); m: Sample mass (g);

[0033] Q -30~-20 =C P ×ΔT

[0034] C P : Specific heat capacity of the sample (J / kg×℃); ΔT is the temperature (℃) at which the sample rises (or falls), such as ΔT = -20 - (-30) = 10 (℃) here;

[0035] ③ Calculate the enthalpy of fusion for each temperature stage based on the calculated specific heat capacity of the sample:

[0036] H m =H t -C P ×ΔT

[0037] H m : Enthalpy of fusion (J) at each temperature stage; H t C P The definition of ΔT is the same as above;

[0038] ④ Based on the calculated enthalpy of fusion for each temperature stage, calculate the freeze-bound water content at the corresponding pore size for each temperature stage:

[0039]

[0040] M: Freeze-bound water content (g / g) at each temperature stage corresponding to the pore size; 334: Heat of fusion of water (J / g).

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The detection method provided by the present invention can directly detect the concentrated M / CNFs without requiring the M / CNFs to be completely dried or redispersed. It can intuitively reflect the changes in pore size distribution of the concentrated M / CNFs and avoid completely drying the micro / nano cellulose.

[0043] (2) This invention fully utilizes the mechanism that water in fiber pores has a lower melting temperature than free water. After CNF concentration, the isothermal step melting procedure of DSC is used to quantitatively detect the distribution of frozen-bound water in the concentrated M / CNFs. This technique helps to better understand the impact of concentration on fiber pore structure. Attached Figure Description

[0044] Figure 1 The heat flow and temperature curves of the 1-10% CNF micro / nanocellulose semisolid in Example 1 are shown.

[0045] Figure 2 The heat flow and temperature curves for the 1-20% CNF micro / nanocellulose semisolids in Example 2 are shown.

[0046] Figure 3 The heat flow and temperature curves of the 2-10% CNF micro / nanocellulose semisolid in Example 3 are shown.

[0047] Figure 4 The heat flow and temperature curves for the 2-30% CNF micro / nanocellulose semisolid in Example 4 are shown.

[0048] Figure 5 This is a distribution diagram of the freeze-bound water in the 1-10% CNF micro / nanocellulose semi-solid of Example 1;

[0049] Figure 6 This is a distribution diagram of the freeze-bound water in the 1-20% CNF micro / nanocellulose semisolid of Example 2;

[0050] Figure 7 This is a distribution diagram of the freeze-bound water in the 2-10% CNF micro / nanocellulose semi-solid of Example 3;

[0051] Figure 8 This is a distribution diagram of the freeze-bound water in the 2-30% CNF micro / nanocellulose semi-solid of Example 4;

[0052] Figure 9 and Figure 10 CNFs, including those from the examples, were prepared to a concentration of 60 g / m³. 2 The stretching curve of the CNF membrane indirectly reflects the effect of the frozen bound water content in the concentrated CNFs on the subsequent stretching properties of CNFs. Detailed Implementation

[0053] The present invention will be further described in detail below with reference to embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto. All raw materials involved in the present invention can be purchased directly from the market. For process parameters not specifically specified, conventional techniques can be referred to.

[0054] This invention does not impose any special restrictions on the type or source of the cellulose pulp used. The following example uses bleached hardwood fiber pulp.

[0055] Example 1

[0056] After thorough disintegration of bleached hardwood pulp, the concentration was adjusted to 1.0 wt% with distilled water. The pulp was then milled 12 times at 2000 rpm using an ultrafine mill with a gap of -120 μm to obtain an M / CNFs suspension. The resulting M / CNFs suspension was concentrated using a plate centrifuge. Centrifugation was performed at 1000 rpm for 20 min, followed by centrifugation at 2000 rpm for 120 min to obtain a micro / nanocellulose semi-solid with a concentration of 10.0 wt%, named 1-10% CNF.

[0057] ~10 mg of 1-10% CNF micro / nanocellulose semi-solid was placed in a sealed crucible and cooled to -30 °C in a differential scanning calorimeter sample pan at a heating rate of 5 °C / min, and held at this temperature for 10 min. Subsequently, the temperature of the sample crucible was sequentially increased to -20 °C, -15 °C, -10 °C, -6 °C, and -4 °C at a heating rate of 1 °C / min, and held at this temperature for 6 min after each increase. Then, the temperature of the sample crucible was sequentially increased to -2 °C, -1.5 °C, -1 °C, -0.5 °C, and -0.1 °C at a heating rate of 1 °C / min, and held at these temperatures for 10 min, 20 min, 20 min, 15 min, and 15 min, respectively.

[0058] Each endothermic peak of the obtained heat flow curve was integrated individually using Origin software. The results are shown in the table below. The content of frozen bound water at each temperature corresponding to the pore size was then calculated using thermodynamic formulas.

[0059] Table 1

[0060]

[0061] The calculation process and results are as follows:

[0062] 1) Calculate the total heat at each temperature stage based on the integral area and sample mass:

[0063] H t =ΔS×m

[0064] H t: Total heat at each temperature stage (J); ΔS: Integral area (J / g); m: Sample mass (g)

[0065] 2) Calculate the specific heat capacity C of the sample. P :

[0066] Because the water in CNFs does not melt in the -30℃ to -20℃ range, the integral result corresponding to this range is used to determine the sensible heat of the sample and to calculate its specific heat capacity C. P :

[0067] Q -30~-20 =ΔS×m

[0068] Q -30~-20 : Heat absorbed by the sample during the -30℃ to -20℃ range (J); ΔS: Integral area (J / g); m: Sample mass (g);

[0069] Q -30~-20 =C P ×ΔT

[0070] C P : Specific heat capacity of the sample (J / kg×℃); ΔT is the temperature (℃) at which the sample rises (or falls), such as ΔT = -20 - (-30) = 10 (℃) here;

[0071] 3) Calculate the enthalpy of fusion for each temperature stage based on the calculated specific heat capacity of the sample:

[0072] H m =H t -C P ×ΔT

[0073] H m Enthalpy of fusion (J) at each temperature stage;

[0074] 4) Based on the calculated enthalpy of fusion for each temperature stage, calculate the freeze-bound water content at the corresponding pore size for each temperature stage:

[0075]

[0076] M: Freeze-bound water content (g / g) at each temperature stage corresponding to the pore size; 334: Heat of fusion of water (J / g);

[0077] The following results were obtained: 0–2.6 nm: 0.0021 g / g, 2.6–4.0 nm: 0.0038 g / g, 4.0–6.6 nm: 0.0076 g / g, 6.6–9.9 nm: 0.0064 g / g, 9.9–19.8 nm: 0.0132 g / g, 19.8–26.4 nm: 0.0045 g / g, 26.4–39.6 nm: 0.0064 g / g, 39.6–79.2 nm: 0.0160 g / g, 79.2–395.8 nm: 0.0385 g / g. This indicates that M / CNFs form pores of different sizes during the concentration process, and their pore size distribution was detected by DSC.

[0078] Example 2

[0079] After thorough disintegration of bleached hardwood pulp, the concentration was adjusted to 1.0 wt% with distilled water. The pulp was then milled 12 times using an ultrafine mill with a gap of -120 μm and a rotation speed of 2000 rpm to obtain an M / CNFs suspension. The resulting M / CNFs suspension was concentrated using a plate centrifuge. After low-speed centrifugation for 20 min and high-speed centrifugation for 120 min, the suspension was transferred to a low-temperature centrifuge and centrifuged at 10000 rpm for 5 min to obtain a micro / nanocellulose semi-solid with a concentration of 20.0 wt%, named 1-20% CNF.

[0080] ~10 mg of 1-20% CNF micro / nanocellulose semi-solid was placed in a sealed crucible and cooled to -30 °C in a differential scanning calorimeter sample pan at a heating rate of 5 °C / min, and held at this temperature for 10 min. Subsequently, the temperature of the sample crucible was sequentially increased to -20 °C, -15 °C, -10 °C, -6 °C, and -4 °C at a heating rate of 1 °C / min, and held at this temperature for 6 min after each increase. Then, the temperature of the sample crucible was sequentially increased to -2 °C, -1.5 °C, -1 °C, -0.5 °C, and -0.1 °C at a heating rate of 1 °C / min, and held at these temperatures for 10 min, 20 min, 20 min, 15 min, and 15 min, respectively.

[0081] Each endothermic peak of the obtained heat flow curve was integrated individually using Origin software. The integration results are shown in the table below. Then, the content of frozen bound water at each temperature corresponding to the pore size was calculated according to the thermodynamic formula.

[0082] Table 2

[0083]

[0084] The calculation process and results are as follows:

[0085] 1) Calculate the total heat at each temperature stage based on the integral area and sample mass:

[0086] H t =ΔS×m

[0087] H t : Total heat at each temperature stage (J); ΔS: Integral area (J / g); m: Sample mass (g)

[0088] 2) Calculate the specific heat capacity C of the sample. P :

[0089] Because the water in CNFs does not melt in the -30℃ to -20℃ range, the integral result corresponding to this range is used to determine the sensible heat of the sample and to calculate its specific heat capacity C. P :

[0090] Q -30~-20 =ΔS×m

[0091] Q -30~-20 : Heat absorbed by the sample during the -30℃ to -20℃ range (J); ΔS: Integral area (J / g); m: Sample mass (g);

[0092] Q -30~-20 =C P ×ΔT

[0093] C P : Specific heat capacity of the sample (J / kg×℃); ΔT is the temperature (℃) at which the sample rises (or falls), such as ΔT = -20 - (-30) = 10 (℃) here;

[0094] 3) Calculate the enthalpy of fusion for each temperature stage based on the calculated specific heat capacity of the sample:

[0095] H m =H t -C P ×ΔT

[0096] H m Enthalpy of fusion (J) at each temperature stage;

[0097] 4) Based on the calculated enthalpy of fusion for each temperature stage, calculate the freeze-bound water content at the corresponding pore size for each temperature stage:

[0098]

[0099] M: Freeze-bound water content (g / g) at each temperature stage corresponding to the pore size; 334: Heat of fusion of water (J / g);

[0100] The following results were obtained: 0–2.6 nm: 0.0032 g / g, 2.6–4.0 nm: 0.0077 g / g, 4.0–6.6 nm: 0.0146 g / g, 6.6–9.9 nm: 0.0142 g / g, 9.9–19.8 nm: 0.0328 g / g, 19.8–26.4 nm: 0.0135 g / g, 26.4–39.6 nm: 0.0227 g / g, 39.6–79.2 nm: 0.0574 g / g, 79.2–395.8 nm: 0.1452 g / g. This indicates that M / CNFs form pores of different sizes during the concentration process, and their pore size distribution was detected by DSC.

[0101] Example 3

[0102] After thorough disintegration of bleached hardwood pulp, the concentration was adjusted to 1.0 wt% with distilled water. The pulp was then milled 12 times using an ultrafine mill with a gap of -120 μm and a rotation speed of 2000 r / min to obtain an M / CNFs suspension. The resulting M / CNFs suspension was concentrated using a plate centrifuge. After low-speed centrifugation for 20 min and high-speed centrifugation for 120 min, a micro / nanocellulose semi-solid with a concentration of 10.0 wt% was obtained, named 1-10% CNF. The obtained 1-10% CNF micro / nanocellulose semi-solid was dispersed to 1.0 wt% with distilled water using a high-speed emulsifier. The dispersed M / CNFs suspension was then further concentrated using a plate centrifuge. After low-speed centrifugation for 20 min and high-speed centrifugation for 120 min, a further concentrated micro / nanocellulose semi-solid with a concentration of 10.0 wt% was obtained, named 2-10% CNF.

[0103] ~10 mg of 2-10% CNF micro / nano cellulose semi-solid was placed in a sealed crucible and cooled to -30 °C in a differential scanning calorimeter sample pan at a heating rate of 5 °C / min, and held at this temperature for 10 min. Subsequently, the temperature of the sample crucible was sequentially increased to -20 °C, -15 °C, -10 °C, -6 °C, and -4 °C at a heating rate of 1 °C / min, and held at this temperature for 6 min after each increase. Then, the temperature of the sample crucible was sequentially increased to -2 °C, -1.5 °C, -1 °C, -0.5 °C, and -0.1 °C at a heating rate of 1 °C / min, and held at these temperatures for 10 min, 20 min, 20 min, 15 min, and 15 min, respectively.

[0104] Each endothermic peak of the obtained heat flow curve was integrated individually using Origin software. The integration results are shown in the table below. Then, the content of frozen bound water at each temperature corresponding to the pore size was calculated according to the thermodynamic formula.

[0105] Table 3

[0106]

[0107] The calculation process and results are as follows:

[0108] 1) Calculate the total heat at each temperature stage based on the integral area and sample mass:

[0109] H t =ΔS×m

[0110] H t : Total heat at each temperature stage (J); ΔS: Integral area (J / g); m: Sample mass (g)

[0111] 2) Calculate the specific heat capacity C of the sample. P :

[0112] Because the water in CNFs does not melt in the -30℃ to -20℃ range, the integral result corresponding to this range is used to determine the sensible heat of the sample and to calculate its specific heat capacity C. P :

[0113] Q -30~-20 =ΔS×m

[0114] Q -30~-20 : Heat absorbed by the sample during the -30℃ to -20℃ range (J); ΔS: Integral area (J / g); m: Sample mass (g);

[0115] Q -30~-20 =C P ×ΔT

[0116] C P : Specific heat capacity of the sample (J / kg×℃); ΔT is the temperature (℃) at which the sample rises (or falls), such as ΔT = -20 - (-30) = 10 (℃) here;

[0117] 3) Calculate the enthalpy of fusion for each temperature stage based on the calculated specific heat capacity of the sample:

[0118] H m =H t -C P ×ΔT

[0119] H m Enthalpy of fusion (J) at each temperature stage;

[0120] 4) Based on the calculated enthalpy of fusion for each temperature stage, calculate the freeze-bound water content at the corresponding pore size for each temperature stage:

[0121]

[0122] M: Freeze-bound water content (g / g) at each temperature stage corresponding to the pore size; 334: Heat of fusion of water (J / g);

[0123] The following results were obtained: 0–2.6 nm: 0.0029 g / g, 2.6–4.0 nm: 0.0053 g / g, 4.0–6.6 nm: 0.0094 g / g, 6.6–9.9 nm: 0.0088 g / g, 9.9–19.8 nm: 0.0184 g / g, 19.8–26.4 nm: 0.0058 g / g, 26.4–39.6 nm: 0.0105 g / g, 39.6–79.2 nm: 0.0224 g / g, 79.2–395.8 nm: 0.0510 g / g. This indicates that M / CNFs form pores of different sizes during the concentration process, and their pore size distribution was detected by DSC.

[0124] Example 4

[0125] After thorough disintegration of bleached hardwood pulp, the concentration was adjusted to 1.0 wt% with distilled water. The pulp was then milled 12 times at 2000 rpm using an ultrafine mill with a gap of -120 μm to obtain an M / CNFs suspension. The resulting M / CNFs suspension was concentrated using a plate centrifuge, centrifuged at low speed for 20 min and then at high speed for 120 min. The concentrate was then transferred to a cryogenic centrifuge and centrifuged at 10000 rpm for 30 min to obtain a micro / nanocellulose semi-solid with a concentration of 30.0 wt%, named 1-30% CNF. The obtained 1-30% CNF micro / nanocellulose semi-solid was dispersed to 1.0 wt% with distilled water using a high-speed emulsifier. The dispersed M / CNFs suspension was further concentrated using a plate centrifuge and a cryogenic centrifuge to obtain a further concentrated micro / nanocellulose semi-solid with a concentration of 30.0 wt%, named 2-30% CNF.

[0126] ~10 mg of 2-30% CNF micro / nanocellulose semi-solid was placed in a sealed crucible and cooled to -30 °C in a differential scanning calorimeter sample pan at a heating rate of 5 °C / min, and held at this temperature for 10 min. Subsequently, the temperature of the sample crucible was sequentially increased to -20 °C, -15 °C, -10 °C, -6 °C, and -4 °C at a heating rate of 1 °C / min, and held at this temperature for 6 min after each increase. Then, the temperature of the sample crucible was sequentially increased to -2 °C, -1.5 °C, -1 °C, -0.5 °C, and -0.1 °C at a heating rate of 1 °C / min, and held at these temperatures for 10 min, 20 min, 20 min, 15 min, and 15 min, respectively.

[0127] Each endothermic peak of the obtained heat flow curve was integrated individually using Origin software. The integration results are shown in the table below. Then, the content of frozen bound water at each temperature corresponding to the pore size was calculated according to the thermodynamic formula.

[0128] Table 4

[0129]

[0130] The calculation process and results are as follows:

[0131] 1) Calculate the total heat at each temperature stage based on the integral area and sample mass:

[0132] H t =ΔS×m

[0133] H t : Total heat at each temperature stage (J); ΔS: Integral area (J / g); m: Sample mass (g)

[0134] 2) Calculate the specific heat capacity C of the sample. P :

[0135] Because the water in CNFs does not melt in the -30℃ to -20℃ range, the integral result corresponding to this range is used to determine the sensible heat of the sample and to calculate its specific heat capacity C. P :

[0136] Q -30~-20 =ΔS×m

[0137] Q -30~-20 : Heat absorbed by the sample during the -30℃ to -20℃ range (J); ΔS: Integral area (J / g); m: Sample mass (g);

[0138] Q -30~-20 =C P ×ΔT

[0139] C P : Specific heat capacity of the sample (J / kg×℃); ΔT is the temperature (℃) at which the sample rises (or falls), such as ΔT = -20 - (-30) = 10 (℃) here;

[0140] 3) Calculate the enthalpy of fusion for each temperature stage based on the calculated specific heat capacity of the sample:

[0141] H m =H t -C P ×ΔT

[0142] H m Enthalpy of fusion (J) at each temperature stage;

[0143] 4) Based on the calculated enthalpy of fusion for each temperature stage, calculate the freeze-bound water content at the corresponding pore size for each temperature stage:

[0144]

[0145] M: Freeze-bound water content (g / g) at each temperature stage corresponding to the pore size; 334: Heat of fusion of water (J / g);

[0146] The following results were obtained: 0–2.6 nm: 0.0046 g / g, 2.6–4.0 nm: 0.0011 g / g, 4.0–6.6 nm: 0.0209 g / g, 6.6–9.9 nm: 0.0207 g / g, 9.9–19.8 nm: 0.0481 g / g, 19.8–26.4 nm: 0.0216 g / g, 26.4–39.6 nm: 0.0381 g / g, 39.6–79.2 nm: 0.0722 g / g, 79.2–395.8 nm: 0.1000 g / g. This indicates that M / CNFs form pores of different sizes during the concentration process, and their pore size distribution was detected by DSC.

[0147] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A method for detecting the pore size distribution during the concentration of micro / nanocellulose, characterized in that... Includes the following steps: (1) The cellulose slurry was milled to obtain a micro / nano cellulose suspension; (2) The suspension obtained in step (1) is concentrated to obtain micro / nanocellulose semi-solid; the solid content of the micro / nanocellulose semi-solid is 10.0 wt%-30.0 wt%; (3) The pore size distribution of the micro / nano cellulose semi-solid obtained in step (2) was detected by the isothermal step melting method of differential scanning calorimetry. The detection method is as follows: the micro / nano cellulose semi-solid was placed in a sealed crucible and heated in the sample pan of the differential scanning calorimeter by the isothermal step melting method to obtain the heat flow and temperature curves. The heating rate was 1℃ / min, the temperature range was -35℃ to 15℃, and the detection time was 1h to 3h. (4) Integrate each endothermic peak of the obtained heat flow curve separately, and calculate the frozen bound water content at each temperature corresponding to the pore size according to the thermodynamic formula; The calculation process based on thermodynamic formulas in step (4) is as follows: Calculate the total heat at each temperature stage based on the integral area and sample mass: , H t ΔS: Total heat at each temperature stage, J; ΔS: Integral area, J / g; m: Sample mass, g; Calculate the specific heat capacity C of the sample. P : Because the water in CNFs does not melt in the -30℃ to -20℃ range, the integral result corresponding to this range is used to determine the sensible heat of the sample and to calculate its specific heat capacity C. P : , Q -30~-20 ΔS: Heat absorbed by the sample in the range of -30℃ to -20℃, J; ΔS: Integral area, J / g; m: Sample mass, g; , C P : Specific heat capacity of the sample, J / kg×℃; ΔT is the temperature at which the sample rises or falls, ℃; for example, ΔT = -20 - (-30) = 10℃ here; The enthalpy of fusion at each temperature stage was calculated based on the calculated specific heat capacity of the sample. , H m Enthalpy of fusion at each temperature stage, J; H t C P The definition of ΔT is the same as above; Based on the calculated enthalpy of fusion for each temperature stage, the freeze-bound water content at the corresponding pore size for each temperature stage was calculated: , M: Freeze-bound water content at each temperature stage and corresponding pore size, g / g; 334: Heat of fusion of water, J / g.

2. The method for detecting pore size distribution during the concentration of micro / nanocellulose according to claim 1, characterized in that, The cellulose pulp in step (1) is made of hardwood fiber, softwood fiber or other biomass-derived cellulose, and the concentration of the pulp after grinding is 0.5 wt%-3.0 wt%.

3. The method for detecting pore size distribution during the concentration of micro / nanocellulose according to claim 1, characterized in that, After the concentration process in step (2), the following steps are also included, followed by detection using differential scanning calorimetry: (a) The obtained semi-solid was redispersed to obtain a redispersed micro / nanocellulose suspension; (b) The suspension obtained in step (a) is concentrated to obtain a secondary concentrated micro / nano cellulose semi-solid.

4. The method for detecting pore size distribution during the concentration of micro / nanocellulose according to claim 3, characterized in that, The redispersibility method described in step (a) is mechanical redispersibility, the concentration of the redispersible micro / nanocellulose suspension is 0.5~3.0wt%, and the dispersion method adopts one or more combinations of high-speed emulsifier, nano homogenizer, ultrafine particle mill and nano-microfluidic homogenizer.

5. The method for detecting pore size distribution during the concentration of micro / nanocellulose according to claim 4, characterized in that, When using a high-speed emulsifier to mechanically redisperse micro / nanocellulose semi-solids, the concentration of the redispersed micro / nanocellulose suspension is 0.7~1.5 wt%, the redispersing rate is 3000~7000 r / min, and the dispersion time is 2~10 min.

6. The method for detecting pore size distribution during the concentration of micro / nanocellulose according to claim 1, characterized in that, The concentration process described in step (b) is either filtration concentration or centrifugal concentration, using one or a combination of vacuum filtration or centrifugation; the concentration time is 30 to 180 minutes.

7. The method for detecting pore size distribution during the concentration of micro / nanocellulose according to claim 3, characterized in that, The solid content of the secondary concentrated micro / nano cellulose semi-solid described in step (b) is 10.0 wt%-30.0 wt%.

8. The method for detecting pore size distribution during the concentration of micro / nanocellulose according to claim 1, characterized in that, The concentration process described in step (2) is either filtration concentration or centrifugal concentration, using one or a combination of vacuum filtration or centrifuge; the concentration time is 30~180 min.